LOCAL FINANCES OF SPATIAL DEVELOPMENT OF TERRITORIAL COMMUNITIES: THEORETICAL AND PRACTICAL RESEARCH - KURYSH, Taras (Bulletin of Taras Shevchenko National University of Kyiv, Geography, 2025)
Background. In the article, the author reveals the current approaches to determining the content of financial resources of local self-government bodies in Ukraine and analyses the regulatory framework and scientific sources on the problem under study. The essence of the most important categories that make up the conceptual apparatus of the study of the spatial development finance of territorial communities is determined. On the basis of the study, the evolution of its development is revealed. Methods. The methods used were the analysis of the legal framework, recent research and publications, induction, historical research and generalisation with justification of the author’s own views and opinions Results. The concepts of basic definitions on the topic under study, which determine the theoretical and spatial aspects of the formation of financial resources of territorial communities in Ukraine, are revealed, taking into account the positions of both Ukrainian and foreign scholars and regulatory documents governing both the process of decentralisation and the possibilities of forming the financial sustainability of territorial communities. The study identifies the components and conditions for ensuring financial self-sufficiency of territorial communities, taking into account current social challenges, and also identifies the basic principles of financial management of territorial communities to ensure their capacity. Conclusions. The process of decentralisation in Ukraine is accompanied by the formation of capable territorial communities that will ensure balanced economic and social development of the respective territory, efficient use of natural, labour and financial resources, development of the community’s human potential, and involvement of the community’s potential to ensure its competitiveness. In the context of a full-scale war and the introduction of martial law, problems arise in the balanced development of communities, taking into account their existing financial capacity and spatial features. It is important to identify shortcomings, establish conditions and principles for managing the financial resources of territorial communities, and assess their ability to withstand external and internal threats to socio-economic development and quality of life.